Early cochlear implantation in prelingual profound hearing loss in Italy, analyzed by means of a social media survey - Orzan, Eva; Pizzamiglio, Giulia; Magadle, Jad; Bubbico, Luciano; Cutler, Jodi M.; Consolino, Patrizia; Burdo, Sandro; Zamagni, Giulia; Magni, Elena; Mariottini, Claudio; Gambacorta, Valeria; Ricci, Giampietro; et al. (Frontiers in Pediatrics, 2023)
Objective: To assess newborn hearing screening (NHS) impact on timing of cochlear implant (CI) surgery of patients with prelingual bilateral profound hearing impairment (BPHI), in order to evaluate whether the NHS ultimately serves the needs of the target population in Italy. Methods: An online questionnaire was created to survey subjects affected by prelingual BPHL born between 1990 and 2018. Questions focused on age at BPHI diagnosis, first and second CI surgery (if performed), and the region in which the surgery was performed. The survey was distributed to potential participants via social media communities used by hearing impaired people or their family members for sharing advice and offering support. Responses were analyzed using descriptive statistics. Results: Among the 318 respondents who completed the questionnaire, 276 (87%) reported having chosen CI surgery, 2/3 of them bilaterally. In the vast majority (97%) of cases the CI is used on a daily basis. Most of the people residing in the center (65%) and southern Italy (71%) had to move from their region of residence to perform the surgery. Late CI surgery was associated with failure to perform NHS (p = 0.007), birth before 2011 (p = 0.009), definitive diagnosis of BPHI after 6 months of life (p = 0.002), and progressive hearing impairment (p <0.001). Conclusion: The worldwide scientific approval of the NHS as the current best opportunity for early diagnosis and CI treatment for prelingual BPHI is confirmed by what patients and families reported via the online questionnaire used for this study. In recent years, early bilateral cochlear implantation has become increasingly available in Italy, but late diagnosis, progressive hearing loss, failure to perform the NHS and lack of follow-up are still open questions. A large part of families has to move from the region of residence to have their child undergo CI surgery, revealing inequalities in terms of geographical disparities. Social media has proved to be a valuable, fast and inexpensive tool for gathering information on the effectiveness of health prevention programs, involving a large sample of individuals in a short amount of time.